2020
DOI: 10.3389/fncel.2020.598517
|View full text |Cite
|
Sign up to set email alerts
|

Stress Granule Dysregulation in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease with no current cure. ALS causes degeneration of both upper and lower motor neurons leading to atrophy of the innervating muscles and progressive paralysis. The exact mechanism of the pathology of ALS is unknown. However, 147 genes have been identified that are causative, associated with, or modify disease progression. While the causative mechanism is unknown, a number of pathological processes have been associated with ALS. These i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
(103 reference statements)
0
36
0
Order By: Relevance
“…SGs play a crucial role in RNA metabolism, notably in translation inhibition through phosphorylation of eukaryotic initiation factor 2α (eIF2α). Originally protective, under chronic stress, the presence of SGs could lead to pathological conditions (for reviews, see [ 214 , 215 , 216 ]). Thus, SGs could act as a seeding mechanism that result in accumulation of RBPs.…”
Section: Fus An Rna-binding Protein Associated With Alsmentioning
confidence: 99%
“…SGs play a crucial role in RNA metabolism, notably in translation inhibition through phosphorylation of eukaryotic initiation factor 2α (eIF2α). Originally protective, under chronic stress, the presence of SGs could lead to pathological conditions (for reviews, see [ 214 , 215 , 216 ]). Thus, SGs could act as a seeding mechanism that result in accumulation of RBPs.…”
Section: Fus An Rna-binding Protein Associated With Alsmentioning
confidence: 99%
“…Since the first identification of superoxide dismutase 1 ( SOD1 ) as an ALS causative gene in 1993 [ 7 ], significant research efforts and advanced genetic approaches have identified mutations in more than 30 genes that cause ALS and frontotemporal dementia (FTD) [ 15 , 16 , 17 , 18 ]. In addition, 147 different gene mutations found in many different pathways have been shown to contribute to the pathogenesis of ALS [ 19 , 20 ]. Although sporadic ALS cases are much more common than familial ALS cases, a portion can be explained by ALS-causing mutations in genes.…”
Section: Rna-binding Proteins and Alsmentioning
confidence: 99%
“…The most common ALS- and FTD-causing gene mutation is a GGGGCC hexanucleotide repeat expansion in the first intron region of the chromosome 9 open reading frame 72 ( C9orf72 ) gene [ 34 , 35 ]. ALS and FTD patients display several hundred to a few thousand copies of the GGGGCC repeat in the C9orf72 gene [ 34 ], and the C9orf72 repeat expansion’s toxicity increases with age, repeat length, and expression level [ 19 , 36 ]. Repeat-containing transcripts of the mutated C9orf72 gene can form RNA foci enriched with RNA-binding proteins in induced pluripotent stem cell (iPSC)-derived neurons from ALS and FTD patients, as well as in motor neurons of C9orf72-ALS patients [ 37 , 38 , 39 , 40 ].…”
Section: Rna-binding Proteins and Alsmentioning
confidence: 99%
See 2 more Smart Citations